Diosgenin protects against cationic bovine serum albumin-induced membranous glomerulonephritis by attenuating oxidative stress and renal inflammation via the NF-κB pathway - Shiyan Jia; Ruihua Si; Guangzhen Liu; Qiming Zhong (Taylor & Francis Group, 2024)
AbstractContext Membranous glomerulonephritis (MGN) is a leading cause of nephrotic syndrome in adults. Diosgenin (DG) has been reported to exert antioxidative and anti-inflammatory effects.Objective To investigate the renoprotective activity of DG in a cationic bovine serum albumin-induced rat model of MGN.Materials and methods Fourty male Sprague-Dawley rats were randomized into four groups. The MGN model was established and treated with a DG dose (10 mg/kg) and a positive control (TPCA1, 10 mg/kg), while normal control and MGN groups received distilled water by gavage for four consecutive weeks. At the end of the experiment, 24 h urinary protein, biochemical indices, oxidation and antioxidant levels, inflammatory parameters, histopathological examination, immunohistochemistry and immunoblotting were evaluated.Results DG significantly ameliorated kidney dysfunction by decreasing urinary protein (0.56-fold), serum creatinine (SCr) (0.78-fold), BUN (0.71-fold), TC (0.66-fold) and TG (0.73-fold) levels, and increasing ALB (1.44-fold). DG also reduced MDA (0.82-fold) and NO (0.83-fold) levels while increasing the activity of SOD (1.56-fold), CAT (1.25-fold), glutathione peroxidase (GPx) (1.55-fold) and GSH (1.81-fold). Furthermore, DG reduced Keap1 (0.76-fold) expression, Nrf2 nuclear translocation (0.79-fold), and induced NQO1 (1.25-fold) and HO-1 (1.46-fold) expression. Additionally, DG decreased IL-2 (0.55-fold), TNF-α (0.80-fold) and IL-6 (0.75-fold) levels, and reduced protein expression of NF-κB p65 (0.80-fold), IKKβ (0.93-fold), p-IKKβ (0.89-fold), ICAM-1 (0.88-fold), VCAM-1 (0.91-fold), MCP-1 (0.88-fold) and E-selectin (0.87-fold), and also inhibited the nuclear translocation of NF-κB p65 (0.64-fold).Discussion and conclusions The results suggest a potential therapeutic benefit of DG against MGN due to the inhibition of the NF-κB pathway, supporting the need for further clinical trials.